Psychosocial and Neurocognitive Factors Associated With Hepatitis C – Implications for Future Health and Wellbeing - Barreira, David Pires; Marinho, Rui Tato; Bicho, Manuel; Fialho, Renata; Ouakinin, Silvia Raquel Soares (Frontiers in Psychology, 2019)
Background: Hepatitis C virus (HCV) infection involves changes not only from the point of view of physical health but also emotional and social that have a significant impact on the quality of life of these patients. According to the literature review, it seems that there is an important association between psychosocial factors, in particular on a cognitive level and disease progression. The aim of this mini-review is to summarize recent literature looking at the associations between psychosocial and neurocognitive factors and HCV. Methods: PubMed/Medline was systematically searched for psychosocial and neurocognitive factors associated with hepatitis C, treatment adherence and patient wellbeing. Results: Patients present with a range of extrahepatic symptoms including fatigue, anxiety, depression and neurocognitive dysfunction. HCV impact on quality of life and wellbeing has serious clinical and social implications. Conclusion: Hepatitis C and its management continue to have a profound impact on health and psychologic wellbeing. Considering the serious extrahepatic implications for individuals, it is imperative that healthcare professionals pay close attention to psychosocial and neurocognitive factors. The focus on combined clinical approaches could enhance understanding about the health and social impacts of hepatitis C along the life course.